The effects of utilizing English language courseware on secondary school students' performance in Iran - Hashemyolia, Shayeshteh (Mediterranean Center of Social and Educational Research, 2014)
The purpose of this study was to determine the effects of Rosetta stone’s English Language Courseware (RSELC) on third grade students’ performance in public secondary school in Iran. More specifically, this study also aimed to evaluate students’ perception about the usefulness of language courseware. This study utilized a quasi-experimental method using only post-test design which consists of two groups. Control group was taught using traditional instruction and experimental group was taught using educational software, namely RSELC. Both groups consist of 31Iranin secondary school students. In addition, A questionnaire was used which developed by researchers. Quantitative analyses revealed that there was significant difference between the groups on the overall performance in favour of experimental group. Based on obtained results, the current study concluded RSELC that was an effective tool for teaching and learning English language at the third grade secondary school in Iran.